Evaluation of healing at molar extraction sites with ridge preservation using a non‐resorbable dense polytetrafluoroethylene membrane: A four‐arm cohort prospective study - Arwa M. Al Hugail; Brian L. Mealey; Christopher Walker; Shaimaa Al Harthi; Mylinh Duong; Marcel Noujeim; David J. Lasho; Thomas J. Prihoda; Guy Huynh‐Ba (Wiley, 2021)
Abstract Objectives To examine ridge dimensional changes and histologic parameters of healing when ridge preservation (RP) was performed at molar sites using dense polytetrafluoroethylene (dPTFE) membrane alone, without a bone graft. Material and Methods Eighteen patients had molar extraction and RP using dPTFE membrane alone. Ridge dimensions were measured using two standardized cone beam computerized tomography (CBCT) scans taken within 72 h and 3 months following extraction. Following a 3‐month healing period, an implant osteotomy was prepared using a trephine drill and bone cores were collected for histological analysis. Four‐arm analyses were performed using data from three previously published study arms of the same research group. Results There was a significant change in the buccal ridge height between the four groups at all aspects of the socket. Alveolar ridge width reduction at 3 mm from crest for all aspects (mesial, midpoint, distal) of the socket showed statistically significant difference for dPTFE alone group compared to the other three groups. Percentage of vital bone formation (62.10%) was significantly greater in dPTFE alone group compared to the other groups. Conclusions RP using dPTFE membrane alone in molar sites with intact socket walls showed successful outcomes in maintaining ridge dimensions and in histologic wound healing.